Faktor-Faktor Pendorong Penerimaan Teknologi Pembangkit Listrik Tenaga Surya (PLTS) Atap di Indonesia - Asri Melati Wijayanti; Iwan Inrawan Wiratmadja (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2023)
Primary energy mix in Indonesia is dominated by fossil fuels, which leads to long-term environmental consequences. To address this issue, renewable energy can be utilized as one of the alternatives. The utilization of renewable energy depends on local potential, which can be assessed through the acceptance of technology. The limited number of users of rooftop solar photovoltaics technology in Indonesia may indicates the presence of unidentified driving factors. Therefore, this research aims to identify the driving factors for the acceptance of rooftop solar photovoltaics technology in Indonesia. Using Partial Least Square Structural Equation Modeling (PLS-SEM), the research findings indicates that the main driving factors for the acceptance of the rooftop solar photovoltaics technology among 167 respondents in Indonesian society who have not yet adopted the technology are price value, social influence, and intention. This research provides insight into the utilization of solar energy in Indonesia, emphasizing the importance of economic factors and social influence.